Construction and characterization of bioluminescent Salmonella Reading outbreak and non-outbreak strains - Abubakar Shitu Isah; Reshma Ramachandran; Anuraj Theradiyil Sukumaran; Aaron S. Kiess; Claudia D. Castañeda; Timothy Boltz; Kenneth S. Macklin; Hossam Abdelhamed; Li Zhang (Microbiology Spectrum)
ABSTRACT Salmonella enterica serotype Reading has recently been identified as a significant foodborne pathogen from contaminated poultry products. There is a critical need for close monitoring of this newly emerged pathogen. This study developed bioluminescent strains of S. Reading for real-time pathogen tracking using bioluminescence imaging. Two strains of S. Reading were used: an outbreak strain and a non-outbreak strain. The chloramphenicol acetyltransferase gene was cloned into the plasmid pBS-slpGFPluxABCDE, which carries luxABCDE operon and an ampicillin resistance gene. The newly constructed plasmid was then transformed into the outbreak and non-outbreak strains of S. Reading by electroporation. The resulting colonies were confirmed by visualizing bioluminescence using an in vivo imaging system and by testing their resistance to chloramphenicol. These strains demonstrated a high bioluminescence level (108–109 Photons/s/cm2/sr) and were tested for growth and plasmid stability by daily subculturing in Luria–Bertani medium with and without antibiotics. The plasmid remained stable for 8 days under non-selective conditions, and growth rates were comparable to non-bioluminescent parent strains in antibiotic-free conditions. However, growth was notably different in the presence of chloramphenicol, indicating successful plasmid retention and function. This study successfully created stable bioluminescent S. Reading strains, marking a significant step forward in monitoring and potentially reducing the spread of this emergent foodborne pathogen in the poultry industry.IMPORTANCESalmonella enterica serotype Reading has recently become a significant foodborne pathogen linked to poultry products. To enhance pathogen monitoring, this study developed bioluminescent strains of S. Reading by inserting the chloramphenicol acetyltransferase gene into a plasmid containing a bioluminescence gene cluster. These modified strains were transformed into outbreak and non-outbreak bacterial strains via electroporation. The bioluminescent strains demonstrated stable plasmid retention and high bioluminescence levels. They also showed growth comparable to their parent strains, even in the absence of antibiotics. These bioluminescent strains could potentially facilitate real-time monitoring and control of S. Reading in poultry industries.